Assessment of the performance of an anoxic-aerobic microalgal-bacterial system treating digestate. (May 2021) - Torres-Franco, Andrés F.; Zuluaga, Maribel; Hernández-Roldán, Diana; Leroy-Freitas, Deborah; Sepúlveda-Muñoz, Cristian A.; Blanco, Saúl; Mota, César R.; Muñoz, Raúl
Abstract: The performance of an anoxic-aerobic microalgal-bacterial system treating synthetic food waste digestate at 10 days of hydraulic retention time via nitrification-denitrification under increasing digestate concentrations of 25%, 50%, and 100% (v/v) was assessed during Stages I, II and III, respectively. The system supported adequate treatment without external CO2 supplementation since sufficient inorganic carbon in the digestate was available for autotrophic growth. High steady-state Total Organic Carbon (TOC) and Total Nitrogen (TN) removal efficiencies of 85–96% and 73–84% were achieved in Stages I and II. Similarly, PO 4 3 − -P removals of 81 ± 15% and 58 ± 4% were recorded during these stages. During Stage III, the average influent concentrations of 815 ± 35 mg TOC·L −1, 610 ± 23 mg TN·L −1, and 46 ± 11 mg PO 4 3 − -P·L −1 induced O2 limiting conditions, resulting in TOC, TN and PO 4 3 − -P removals of 85 ± 3%, 73 ± 3%, and 28 ± 16%, respectively. Digestate concentrations of 25% and 50% favored nitrification-denitrification mechanisms, whereas the treatment of undiluted digestate resulted in higher ammonia volatilization and hampered nitrification-denitrification. In Stages I and II, the microalgal community was dominated by Chlorella vulgaris and Cryptomonas sp., whereas Pseudoanabaena sp. was more abundant during Stage III. Illumina sequencing revealed the presence of carbon and nitrogen transforming bacteria, with dominances of the genera Gemmata, Azospirillum, and Psychrobacter during Stage I, II, and III, respectively. Finally, the high settleability of the biomass (98% of suspended solids removal in the settler) and average C (42%), N (7%), P (0.2%), and S (0.4%) contents recovered in the biomass confirmed its potential for agricultural applications, contributing to a closed-cycle management of food waste. Graphical abstract: Image 1 Highlights: 4 and 2-fold diluted digestate was efficiently treated in an anoxic-aerobic system. Undiluted digestate treatment inhibited nitrification and favored NH3 stripping. Chlorella vulgaris and Proteobacteria dominated the microalgal-bacterial community. Nutrients recovery as microalgal-bacterial biomass was quantified via mass balances.